Imaging of gynecological disorders in infants and children - Blair, Joanne C.; Garden, Anne S.; Mann, Gurdeep S. (Medical Radiology, 2012)
This textbook provides a comprehensive review of gynecological imaging in infancy, childhood, and adolescence. Experts from the disciplines of pediatric radiology, gynecology, surgery, and endocrinology have come together to produce a textbook that, while written primarily from the perspective of the radiologist, will be of interest to all professionals involved in the management of these patients. The normal development of the female reproductive tract is described in detail through embryological development, normal childhood appearances, and puberty. Congenital abnormalities are addressed in chapters reviewing structural abnormalities of the reproductive tract and disorders of sex development. A symptoms-based approach is followed in chapters devoted to the assessment of the patient with gynecological pain and disorders of menstruation. Disorders of the breast and the imaging of patients with gynecological neoplasia are considered in dedicated chapters. The specialty of pediatric gynecology is evolving rapidly, drawing on the skills and expertise of professionals from a wide range of specialties. This textbook should prove valuable to all who are involved in this new field of medicine.